Implementation of total quality management and importance-performance analysis for technical service optimization in a maintenance workshop : a case study of PT XYZ - Khadafi, M; Away, Yuwaldi; Dirhamsyah, M (Jurnal Polimesin, 2025)
Customer satisfaction is a key factor of success in service-based industries and is equally important in technical service environments such as PT XYZ’s mechanical repair workshop, which provides civil works, welding, machinery, and valve maintenance services. This study aims to assess service quality and identify the primary factors influencing customer satisfaction, with the objective of formulating strategic improvements tailored to the workshop setting. A quantitative research approach was adopted, incorporating the SERVQUAL dimensions and the Total Quality Management (TQM) framework, while customer loyalty was measured using the Net Promoter Score (NPS). The study involved 93 internal respondents from various organizational units, with work experience ranging from less than five years to more than twenty years. Results indicate a high level of satisfaction, with a Net Promoter Score of 57.29% and an Internal Customer Satisfaction (ICS) Index of 86.9%. Multiple linear regression analysis showed that service quality and Total Quality Management collectively explained 84.3% of the variance in customer satisfaction. Importance and Performance Analysis (IPA) identified education and training, customer focus, and reliability as the top strategic improvement priorities. From an operational perspective, the most frequently requested services included pump shaft fabrication (item code 63-GA-6004, 30 hours), shaft sleeve fabrication (63-GA-6004, 16 hours), and shaft sleeve fabrication (56-GA-4002, initially 36 hours). Following the implementation of these improvements, the workshop achieved a 20 percent reduction in average processing time and completed 182 service activities within two months, significantly enhancing operational efficiency and customer satisfaction.